An Investigation on Mechanical Properties and Durability of Concrete Containing Silica Fume and Fly Ash - Ali Sadr Momtazi; Behzad Tahmouresi; Reza Kohani Khoshkbijari (Civil Engineering Journal, 2016)
Nowadays pozzolans are used vastly in civil projects. Pozzolan is a natural or artificial material containing active silica that increase the strength and improves some properties of concrete. In this survey for investigating some important properties of concrete, silica fume and fly ash was used in replacement of cement in different weights. Concrete compositions were made with water-cement ratio of 0.45 and cured under the same conditions. The main focus of this survey is to investigate the individual and combined effect of using Pozzolan on mechanical properties, permeability and shrinkage of concrete. The mechanical properties of concrete in compressive and bending strength at the age of 7, 28 and 90 days, were evaluated. Permeability was investigated with the water absorption test. The drying shrinkage of concrete was monitored for 90 days. Scanning Electron Microscopy (SEM) images was used in concrete cement based matrix morphology. The results showed that the addition of pozzolan increases the mechanical strength and reduce permeability and increase the drying shrinkage in some mixtures.